Cutting tool and method of manufacturing the same
Patent Information
- Application Number
- CN202611479307.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-30
AI Technical Summary
但现有CVD高铝氮化钛铝涂层的结构设计单一,高铝组分占比过高会导致涂层存在明显的性能短板与技术缺陷
Smart Images

Figure CN123005338A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of cutting tool coating technology, and more specifically, to cutting tools and methods for preparing them. Background Technology
[0002] Titanium nitride aluminum coating is an indispensable key functional material for modern metal cutting tools. The aluminum element in the titanium nitride aluminum coating can react with oxygen to form a dense alumina protective film on the coating surface. This film effectively blocks oxygen diffusion inward, thus significantly improving the coating's oxidation resistance and resistance to crater wear. Therefore, the higher the aluminum content, the more outstanding the high-temperature performance and hardness of the coating. Depending on the preparation technology, the coating's performance varies significantly. Currently, there are two main technical routes for preparing titanium nitride aluminum coatings: physical vapor deposition (PVD) and chemical vapor deposition (CVD). Traditional PVD technology is limited by thermodynamic conditions, and the molar fraction of aluminum can usually only be stabilized at around 0.67-0.70. CVD technology is currently the most effective route for preparing high-alumina face-centered cubic titanium nitride aluminum coatings.
[0003] CVD high-alumina titanium nitride aluminum coatings effectively improve microhardness due to their significant solid solution strengthening effect, while oxidation resistance is significantly enhanced with increasing aluminum content. However, existing CVD high-alumina titanium nitride aluminum coatings have a simplistic structural design, and excessively high aluminum content leads to significant performance shortcomings and technical defects. On the one hand, excessively high overall aluminum content severely reduces the coating's thermal stability. Under high-temperature machining conditions such as high-speed cutting and dry cutting, the coating is prone to metastable cubic phase to hexagonal aluminum nitride (h-AlN) transformation, resulting in decreased mechanical properties and accelerated tool wear. On the other hand, while the strong solid solution strengthening effect of high aluminum content increases coating hardness, it can also increase brittleness. This makes traditional high-alumina titanium nitride aluminum coatings more prone to cracking and chipping under intermittent cutting and high-impact load machining scenarios, leading to reduced service life. Therefore, how to improve the coating's hardness, toughness, and thermal stability while maintaining high aluminum content has become a key technical challenge that urgently needs to be addressed.
[0004] It should be noted that the above statements are only used to provide background information related to this application and do not necessarily constitute prior art. Summary of the Invention
[0005] In a first aspect, this application provides a cutting tool comprising: a substrate; and a coating located on at least a portion of the surface of the substrate, the coating comprising: a titanium aluminum nitride coating, the titanium aluminum nitride coating comprising: Ti 1- q Al qN, 0.7 ≤ q < 1, the titanium aluminum nitride coating comprises alternating layers and spacer layers stacked alternately, the absolute value of the difference between the number of alternating layers and the number of spacer layers is not greater than 1, the alternating layer comprises alternating first sub-layers and second sub-layers stacked alternately, the absolute value of the difference between the number of first sub-layers and the number of second sub-layers is not greater than 1, the first sub-layer comprises Ti 1-x Al x N, 0.6 ≤ x ≤ 0.95, the second sublayer includes Ti 1-y Al y N, 0.1≤y≤0.5, the spacer layer includes Ti 1- z Al z For N, 0≤z≤0.1, the lattice mismatch between the first sublayer and the second sublayer is 0.4%-4.2%; the lattice mismatch between the first sublayer and the spacer layer is 2.0%-4.6%; and the lattice mismatch between the second sublayer and the spacer layer is 0%-2.4%.
[0006] Therefore, Ti 1-q Al q The N-layer grains exhibit a periodic, layered stacking structure with varying composition. The extremely low aluminum content in the face-centered cubic spacer layers provides a lattice template constraint effect for the adjacent first and second sublayers, suppressing the nucleation and growth of hexagonal aluminum nitride (h-AlN) phase in these layers. Simultaneously, the low-aluminum spacer layers demonstrate excellent thermal stability, enhancing the overall thermal stability of the coating system. Furthermore, the spacer layers exhibit good toughness, improving the overall toughness of the coating and resisting cutting impacts. This results in a coating that simultaneously possesses high hardness, excellent thermal stability, and good toughness. The low lattice mismatch between layers reflects a stable epitaxial growth relationship between crystal planes, thermodynamically stabilizing the high-aluminum face-centered cubic phase through a multilayered constraint structure. This superlattice structure maintains a high overall average aluminum content (q≥0.7) while ensuring each layer retains a face-centered cubic structure. This improves the chipping resistance, wear resistance, high-temperature resistance, and overall service life of cutting tools, making them suitable for various metal cutting scenarios and applicable to a wide range of applications.
[0007] In some embodiments, the number of alternating layers is 5 to 100; and / or, the number of the first sub-layer is 8 to 200.
[0008] Thus, through the design of a multi-layer structure, the periodic layered stacking structure extends from the bottom of the grain to the top of the grain, creating a highly coherent interface, enabling the titanium nitride aluminum coating to possess both high hardness and high toughness.
[0009] In some embodiments, Ti in the first sub-layer 1-x Al xN, Ti in the second sublayer 1-y Al y N, Ti in the spacer layer 1-z Al z N is a face-centered cubic structure, each independently.
[0010] Therefore, the first sublayer, the second sublayer, and the spacer layer are all face-centered cubic structures, which gives the formed titanium aluminum nitride coating a clear and flat coherent interface. The titanium aluminum nitride coating has excellent toughness and can effectively extend the life of cutting tools.
[0011] In some embodiments, the crystal plane relationship between the first sublayer and the second sublayer is {001}Ti. 1-x Al x N / / {001}Ti 1-y Al y N; and / or, the crystal plane relationship between the first sublayer and the spacer layer is {001}Ti. 1-x Al x N / / {001}Ti 1-z Al z N; and / or, the crystal plane relationship between the second sublayer and the spacer layer is {001}Ti. 1-y Al y N / / {001}Ti 1- z Al z N.
[0012] Thus, the first sublayer, the second sublayer, and the spacer layer grow epitaxially parallel to the {001} crystal plane of the grain. The continuous {001} crystal plane orientation helps the layers of the titanium nitride aluminum coating to work together in a consistent manner during deformation, reducing the generation and propagation of cracks at the interlayer interface, enhancing the fracture resistance of the titanium nitride aluminum coating, thereby improving the adhesion between the coating and the substrate, and improving the toughness and anti-stripping performance of the cutting tool.
[0013] In some embodiments, the crystal orientation relationship between the first sublayer and the second sublayer is as follows: <010> Ti 1-x Al x N / / <010> Ti 1-y Al y N; and / or, the crystal orientation relationship between the first sublayer and the spacer layer is: <010> Ti 1-x Al x N / / <010> Ti 1-z Al z N; and / or, the crystal orientation relationship between the second sublayer and the spacer layer is as follows: <010> Ti 1-y Al y N / / <010> Ti 1-z Al z N.
[0014] As a result, the crystal orientation of the grains in the first sublayer, the second sublayer, and the spacer layer is consistent, forming a superlattice structure. This facilitates the uniform transfer of load between the layers of the titanium aluminum nitride coating, reduces the sudden increase of stress at the interface, and thus improves the fatigue resistance and crack propagation resistance of the titanium aluminum nitride coating. It also enhances the adhesion between the titanium aluminum nitride coating and the underlayer and functional layers, making the coating more resistant to impact and peeling during machining with cutting tools.
[0015] In some embodiments, the surface of the titanium aluminum nitride coating away from the substrate is defined as a first plane, and a second plane parallel to the first plane is located on the side of the first plane facing the substrate. The minimum distance between the first plane and the second plane is not greater than 60% of the thickness of the titanium aluminum nitride coating. The titanium aluminum nitride coating is positioned along any polished section on the second plane. <111> The cross-sectional area of grains with a crystal orientation and an angle less than 10° with the normal of the first plane accounts for not less than 60% of the total cross-sectional area of the grains; and / or, the texture coefficients TC(200) on the (200) crystal plane, TC(220) on the (220) crystal plane, TC(311) on the (311) crystal plane, TC(331) on the (331) crystal plane, TC(420) on the (420) crystal plane, and TC(111) on the (111) crystal plane satisfy the following: TC(200)≤0.5, 0.2≤TC(220)≤0.7, 0.5≤TC(311)≤1, TC(331)≤0.5, TC(420)≤0.5, TC(111) / TC(311)≥3.
[0016] Therefore, the consistent grain orientation of the titanium nitride aluminum coating can reduce stress concentration and crack propagation problems, improve the stability of the titanium nitride aluminum coating in high-speed cutting, and extend the life of the cutting tool when cutting difficult-to-machine materials. A specific texture factor can simultaneously improve the hardness and toughness of the coating.
[0017] In some embodiments, the Ti in the titanium aluminum nitride coating 1-q Al q The grain size of N is not greater than 2.5 μm; and / or the hardness of the titanium aluminum nitride coating is not less than 30 GPa; and / or the compressive stress of the titanium aluminum nitride coating is 0.5 GPa-3 GPa.
[0018] Therefore, the titanium nitride aluminum coating can significantly improve the hardness of the coating by utilizing the fine grain strengthening effect brought about by the low grain size. At the same time, the high hardness of the titanium nitride aluminum coating greatly improves the coating's resistance to plastic deformation and wear. The moderate compressive stress of the titanium nitride aluminum coating can make the coating less prone to peeling and can effectively inhibit the generation of coating cracks.
[0019] In some embodiments, the thickness of the titanium aluminum nitride coating is 0.5 μm-30 μm; and / or, the sum of the thicknesses of the alternating single layer and the adjacent single spacer layer is 100 nm-1000 nm; and / or, the thickness of the first sublayer is 1 nm-20 nm; and / or, the thickness of the second sublayer is 0.5 nm-10 nm; and / or, the thickness of the spacer layer is 20 nm-300 nm.
[0020] Therefore, by limiting the thickness of each layer, the structural stability of the titanium nitride aluminum coating is improved, and the titanium nitride aluminum coating can have both high oxidation resistance, thermal stability and high strength and toughness.
[0021] In some embodiments, the coating further includes: a base coat located between the substrate and the titanium aluminum nitride coating, the base coat including a nitride coating; and / or a functional layer located on the side of the titanium aluminum nitride coating away from the substrate, the functional layer including one or more of a nitride coating and an antioxidant coating, the antioxidant coating including one or more of an alumina coating and a zirconium oxide coating.
[0022] Therefore, by setting a base layer in the coating, the corrosion of the substrate by ammonia gas during the vapor deposition of titanium nitride aluminum coating can be reduced, better protecting the integrity of the substrate. The titanium nitride coating and titanium nitride aluminum coating have good lattice matching and compositional compatibility, providing a stable adhesion substrate for the nucleation and growth of the titanium nitride aluminum coating, significantly improving the overall film-substrate adhesion and structural stability of the coating. In the functional layer, the nitride coating acts as a transition layer, alleviating the structural mismatch between the titanium nitride aluminum coating and the anti-oxidation coating. The anti-oxidation coating enhances the coating's resistance to high-temperature oxidation, and the outermost nitride coating improves the coating's wear resistance and also serves a decorative purpose.
[0023] In a second aspect of this application, a method for preparing the aforementioned cutting tool is proposed, comprising: performing a vapor deposition treatment on a substrate to obtain a titanium aluminum nitride coating to obtain the cutting tool, wherein the vapor deposition treatment includes alternating first vapor deposition treatment and second vapor deposition treatment, wherein the gas of the first vapor deposition treatment includes TiCl4, AlCl3, NH3, and H2, and the gas of the second vapor deposition treatment includes TiCl4, NH3, H2, and optionally AlCl3, comprising 0.03%-0.08% TiCl4, 0.20%-0.70% AlCl3, and 0.80%-1.20% NH3 based on the total volume of the gas of the first vapor deposition treatment, and comprising 0.03%-0.08% TiCl4, 0%-0.30% AlCl3, and 0.80%-1.20% NH3 based on the total volume of the gas of the second vapor deposition treatment.
[0024] Therefore, by adjusting the AlCl3 gas flow rate of the first and second vapor deposition processes, alternating and spaced layers of titanium nitride aluminum coatings with different aluminum contents can be obtained. A high-aluminum-content titanium nitride aluminum coating was obtained by chemical vapor deposition, which effectively improved the hardness and oxidation resistance of the titanium nitride aluminum coating and extended the service life of cutting tools.
[0025] In some embodiments, the deposition temperature of the first vapor deposition treatment is 700℃-800℃, the deposition pressure of the first vapor deposition treatment is 2mbar-15mbar, and the deposition time of the first vapor deposition treatment is 1min-30min; and / or, the deposition temperature of the second vapor deposition treatment is 730℃-800℃, the deposition pressure of the second vapor deposition treatment is 2mbar-15mbar, and the deposition time of the second vapor deposition treatment is 0.2min-3min; and / or, the number of times the first vapor deposition treatment and the second vapor deposition treatment are alternated is 5-100 times.
[0026] Therefore, by adjusting the deposition parameters of the first vapor deposition process and the second vapor deposition process, a titanium aluminum nitride coating with a periodic layered stacking structure can be obtained.
[0027] In some embodiments, prior to performing vapor deposition on the substrate, the method further includes: performing vapor deposition on the substrate to form an underlayer, the underlayer being located on at least a portion of the surface of the substrate and between the substrate and the titanium aluminum nitride coating; and / or, after performing vapor deposition on the substrate, the method further includes: performing a third vapor deposition on the side of the titanium aluminum nitride coating away from the substrate to form a functional layer, the functional layer including one or more of a nitride coating and an antioxidant coating, the antioxidant coating including one or more of an alumina coating and a zirconium oxide coating.
[0028] Therefore, by performing vapor deposition to obtain the underlayer before preparing the titanium aluminum nitride coating, the protective effect on the substrate can be better exerted. After preparing the titanium aluminum nitride coating, vapor deposition is performed to obtain the functional layer, which is beneficial to improving the coating's anti-oxidation performance, wear resistance, and decorative performance. The titanium aluminum nitride coating, the underlayer, and the functional layer together improve the overall adhesion and stability of the coating. Attached Figure Description
[0029] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, wherein, Figure 1 The image shows a scanning electron microscope (SEM) image of the fracture morphology of the cutting tool prepared in Example 1 of this application.
[0030] Figure 2 Scanning electron microscope image of the surface morphology of the cutting tool prepared in Example 1 of this application.
[0031] Figure 3 This is a scanning electron microscope image of the surface morphology of the titanium aluminum nitride coating in the cutting tool prepared in Example 1 of this application.
[0032] Figure 4 Scanning electron microscope (SEM) image of the polished and etched cross section of the titanium aluminum nitride coating in the cutting tool prepared in Example 1 of this application.
[0033] Figure 5 Scanning transmission electron microscopy (STEM) image of the titanium aluminum nitride coating in the cutting tool prepared in Example 1 of this application – high-angle annular dark field image.
[0034] Figure 6 This is a transmission electron microscope (TEM) image of the titanium aluminum nitride coating in the cutting tool prepared in Example 1 of this application.
[0035] Figure 7 This is a fast Fourier transform diagram of the titanium aluminum nitride coating in the cutting tool prepared in Example 1 of this application. Detailed Implementation
[0036] The embodiments of this application are described in detail below, with examples of these embodiments shown in the accompanying drawings. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0037] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used in this application is for the purpose of describing particular embodiments only and is not intended to limit the application; unless otherwise stated, the values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (e.g., they can be tested according to the methods given in the embodiments of this application).
[0038] The terms “comprising” and “having”, and any variations thereof, in the specification and claims of this application are open-ended expressions, meaning they include what is specified in this application but do not exclude other aspects.
[0039] In the description of this application, all figures disclosed herein, whether or not the words "approximately" or "about" are used, are approximate values. Each figure may vary by less than 10% or by a difference that is considered reasonable by one of the art, such as 1%, 2%, 3%, 4%, or 5%.
[0040] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60~120 and 80~110 are listed for a specific parameter, it is also expected that ranges of 60~110 and 80~120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1~3, 1~4, 1~5, 2~3, 2~4, and 2~5. In this application, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0~5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0041] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. "First feature" and "second feature" may include one or more of the indicated feature.
[0042] In the description of this application, "multiple" means two or more.
[0043] In the description of this application, "A and / or B" can include any of the cases of A alone, B alone, or A and B, where A and B are merely examples and can be any technical feature connected by "and / or" in this application.
[0044] In this application, the order in which the steps are written does not imply a strict execution order and does not limit the implementation process in any way. The specific execution order of each step should be determined by its function and possible internal logic. Unless otherwise specified, all steps in this application can be performed sequentially or randomly, preferably sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if the method may also include step (c), it means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0045] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0046] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0047] In related technologies, the high-alumina titanium nitride coating on the surface of cutting tools has a simple structural design. Under the high-temperature environment generated by high-speed cutting, the aluminum element in the titanium nitride coating can react with oxygen to form a dense alumina protective film on the coating surface. This film can effectively block oxygen diffusion inward, thereby significantly improving the coating's oxidation resistance and resistance to crater wear. Therefore, the higher the aluminum content, the more outstanding the high-temperature performance and hardness of the coating. However, excessive aluminum content will lead to obvious performance shortcomings and technical defects in the titanium nitride coating. On the one hand, excessive aluminum content in the titanium nitride coating will seriously reduce the thermal stability of the coating. On the other hand, the strong solid solution strengthening effect brought by the high aluminum component, while increasing the hardness of the titanium nitride coating, will also lead to increased brittleness of the titanium nitride coating, resulting in a significant reduction in the life of the cutting tool.
[0048] This application proposes a cutting tool whose coating comprises at least one layer of Ti with a face-centered cubic structure deposited by CVD. 1-q Al q N layers, 0.7 ≤ q < 1, Ti 1-q Al q The N-layer has a periodic layered stacked structure with different compositions inside the grains, and the crystal orientation of each layer is consistent. This gives the titanium nitride aluminum coating high aluminum content, high hardness, thermal stability and toughness, which greatly improves the overall service life of cutting tools. It is suitable for various metal cutting processing scenarios and has a wide range of applications.
[0049] In a first aspect, this application provides a cutting tool comprising: a substrate; and a coating located on at least a portion of the surface of the substrate, the coating comprising: a titanium aluminum nitride coating, the titanium aluminum nitride coating comprising: Ti 1- q Al q N, 0.7 ≤ q < 1, the titanium aluminum nitride coating comprises alternating layers and spacer layers stacked alternately, the absolute value of the difference between the number of alternating layers and the number of spacer layers is not greater than 1, the alternating layer comprises alternating first sub-layers and second sub-layers stacked alternately, the absolute value of the difference between the number of first sub-layers and the number of second sub-layers is not greater than 1, the first sub-layer comprises Ti 1-x Al x N, 0.6 ≤ x ≤ 0.95, the second sublayer includes Ti 1-y Aly N, 0.1≤y≤0.5, the spacer layer includes Ti 1- z Al z N, 0 ≤ z ≤ 0.1.
[0050] Therefore, Ti 1-q Al q The N-layer grains have a periodic layered stacking structure with differentiated composition. The crystals in each layer are oriented in the same way, forming a stable superlattice structure. The spacer layer with low aluminum content has excellent thermal stability, which can improve the thermal stability of the entire coating system. At the same time, the spacer layer has good toughness, which can improve the overall toughness of the coating and resist cutting impact. Thus, the overall coating can simultaneously obtain high hardness, excellent thermal stability and good toughness, which greatly improves the chipping resistance, wear resistance, high temperature resistance and overall service life of the cutting tool. The cutting tool can be used in various metal cutting processing scenarios and has a wide range of applications.
[0051] As an example, the Ti 1-q Al q In N, q can be any point value among 0.7, 0.8, and 0.9, or a range of values between any two.
[0052] As an example, the absolute value of the difference between the number of alternating layers and the number of interval layers can be either 0 or 1.
[0053] As an example, the absolute value of the difference between the number of layers of the first sub-layer and the second sub-layer can be either 0 or 1.
[0054] As an example, the Ti 1-x Al x In N, x can be any point value from 0.6, 0.7, 0.8, 0.95, or a range between any two.
[0055] As an example, the Ti 1-y Al y In N, y can be any point value from 0.1, 0.2, 0.3, 0.4, 0.5, or a range of values between any two.
[0056] As an example, the Ti 1-z Al z In N, z can be any point value from 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, or a range between any two.
[0057] In some embodiments, the lattice mismatch between the first sublayer and the second sublayer is 0.4%-4.2%; the lattice mismatch between the first sublayer and the spacer layer is 2.0%-4.6%; and the lattice mismatch between the second sublayer and the spacer layer is 0%-2.4%.
[0058] Therefore, a lower lattice mismatch is beneficial for forming coherent or semi-coherent interfaces between the layers of the titanium aluminum nitride coating. The lower interfacial energy of coherent or semi-coherent interfaces can reduce stress concentration and crystal defects caused by lattice distortion, thereby enhancing the bonding strength between layers.
[0059] As an example, the lattice mismatch between the first sublayer and the second sublayer can be any one of the following values or a range between any two: 0.4%, 0.82%, 1.24%, 1.67%, 2.09%, 2.51%, 2.93%, 3.36%, 3.78%, and 4.2%.
[0060] As an example, the lattice mismatch between the first sublayer and the spacer layer can be any one of 2.0%, 2.29%, 2.58%, 2.87%, 3.16%, 3.44%, 3.73%, 4.02%, 4.31%, or 4.6%, or a range between any two.
[0061] As an example, the lattice mismatch between the second sublayer and the spacer layer can be any one of the following values or a range between any two: 0%, 0.27%, 0.53%, 0.80%, 1.07%, 1.33%, 1.60%, 1.87%, 2.13%, and 2.40%.
[0062] In some embodiments, the titanium aluminum nitride coating has a columnar crystal structure perpendicular to the coating surface.
[0063] In some embodiments, the substrate includes one or more of cemented carbide, cermet, ceramic, and superhard materials.
[0064] In some embodiments, the number of alternating layers is 5 to 100. As an example, the number of alternating layers can be any one of 5, 15, 25, 35, 45, 55, 65, 75, 85, 95, or 100 layers, or a range between any two.
[0065] In some embodiments, the number of layers in the first sub-layer is 8 to 200. As an example, the number of layers in the first sub-layer can be any one of 8, 18, 28, 38, 48, 58, 68, 78, 88, 98, 108, 118, 128, 138, 148, 158, 168, 178, 188, 198, or 200 layers, or a range between any two.
[0066] Thus, through the design of a multi-layer structure, the periodic layered stacking structure extends from the bottom of the grain to the top of the grain, creating a highly coherent interface, enabling the titanium nitride aluminum coating to possess both high hardness and high toughness.
[0067] In some embodiments, Ti in the first sub-layer 1-x Al x N, Ti in the second sublayer 1-y Al y N, Ti in the spacer layer 1-z Al z N is a face-centered cubic structure, each independently.
[0068] Therefore, the first sublayer, the second sublayer, and the spacer layer are all face-centered cubic structures, which gives the formed titanium aluminum nitride coating a clear and flat coherent interface. The titanium aluminum nitride coating has excellent toughness and can effectively extend the life of cutting tools.
[0069] In some embodiments, the crystal plane relationship between the first sublayer and the second sublayer is {001}Ti. 1-x Al x N / / {001}Ti 1-y Al y N; and / or, the crystal plane relationship between the first sublayer and the spacer layer is {001}Ti. 1-x Al x N / / {001}Ti 1-z Al z N; and / or, the crystal plane relationship between the second sublayer and the spacer layer is {001}Ti. 1-y Al y N / / {001}Ti 1- z Al z N.
[0070] Thus, the first sublayer, the second sublayer, and the spacer layer grow epitaxially parallel to the {001} crystal plane of the grain. The continuous {001} crystal plane orientation helps the layers of the titanium nitride aluminum coating to work together in a consistent manner during deformation, reducing the generation and propagation of cracks at the interlayer interface, enhancing the fracture resistance of the titanium nitride aluminum coating, thereby improving the adhesion between the coating and the substrate, and improving the toughness and anti-stripping performance of the cutting tool.
[0071] In some embodiments, the crystal orientation relationship between the first sublayer and the second sublayer is as follows: <010> Ti 1-x Al x N / / <010> Ti 1-y Al y N; and / or, the crystal orientation relationship between the first sublayer and the spacer layer is: <010> Ti 1-x Al x N / / <010> Ti 1-z Al z N; and / or, the crystal orientation relationship between the second sublayer and the spacer layer is as follows: <010> Ti 1-y Al y N / / <010> Ti 1- z Al z N.
[0072] As a result, the crystal orientation of the grains in the first sublayer, the second sublayer, and the spacer layer is consistent, forming a superlattice structure. This facilitates the uniform transfer of load between the layers of the titanium aluminum nitride coating, reduces the sudden increase of stress at the interface, and thus improves the fatigue resistance and crack propagation resistance of the titanium aluminum nitride coating. It also enhances the adhesion between the titanium aluminum nitride coating and the underlayer and functional layers, making the coating more resistant to impact and peeling during machining with cutting tools.
[0073] In some embodiments, the first sublayer, the second sublayer, and the spacer layer are grown epitaxially.
[0074] In some embodiments, the surface of the titanium aluminum nitride coating away from the substrate is defined as a first plane, and a second plane parallel to the first plane is located on the side of the first plane facing the substrate. The minimum distance between the first plane and the second plane is not greater than 60% of the thickness of the titanium aluminum nitride coating. The titanium aluminum nitride coating is positioned along any polished section on the second plane. <111> The cross-sectional area of grains with a crystal orientation and an angle of less than 10° with the normal of the first plane accounts for no less than 60% of the total cross-sectional area of grains.
[0075] As an example, the titanium nitride aluminum coating along any polished section on the second plane <111> The ratio of the cross-sectional area of grains with a crystal orientation and an angle of less than 10° with the normal of the first plane to the total cross-sectional area of grains can be any one of 60%, 70%, 80%, 90%, 100% or any range between two.
[0076] In some embodiments, the texture coefficients TC(200) on the (200) crystal plane, TC(220) on the (220) crystal plane, TC(311) on the (311) crystal plane, TC(331) on the (331) crystal plane, TC(420) on the (420) crystal plane, and TC(111) on the (111) crystal plane of the titanium aluminum nitride coating satisfy the following: TC(200)≤0.5, 0.2≤TC(220)≤0.7, 0.5≤TC(311)≤1, TC(331)≤0.5, TC(420)≤0.5, and TC(111) / TC(311)≥3.
[0077] Therefore, the consistent grain orientation of the titanium nitride aluminum coating can reduce stress concentration and crack propagation problems, improve the stability of the titanium nitride aluminum coating in high-speed cutting, and extend the life of the cutting tool when cutting difficult-to-machine materials. A specific texture factor can simultaneously improve the hardness and toughness of the coating.
[0078] As an example, TC(200) can be any one of the point values of 0.1, 0.2, 0.3, 0.4, 0.5 or any range of values between the two.
[0079] As an example, TC(220) can be any one of the point values of 0.2, 0.3, 0.4, 0.5, 0.6, 0.7 or any range between the two.
[0080] As an example, TC(311) can be any point value among 0.5, 0.6, 0.7, 0.8, 0.9, and 1.0, or a range of values between any two.
[0081] As an example, TC(331) can be any one of the point values of 0.1, 0.2, 0.3, 0.4, 0.5 or any range of values between two of them.
[0082] As an example, TC(420) can be any one of the point values of 0.1, 0.2, 0.3, 0.4, 0.5 or any range of values between two of them.
[0083] As an example, TC(111) / TC(311) can be any one of the point values of 3, 4, and 5, or any range value between the two.
[0084] The texture factor is defined as follows:
[0085] In the formula: TC(hkl) is the texture coefficient; I(hkl) is the reflection intensity of the (hkl) reflective crystal plane obtained by X-ray diffraction measurement; I0(hkl) is the standard intensity of diffraction reflection according to PDF (Powder Diffraction Data Card) card number 46-1200; n is the number of reflecting crystal planes used in the calculation; The (hkl) reflective crystal planes used are (111), (200), (220), (311), (331), and (420).
[0086] In some embodiments, the Ti in the titanium aluminum nitride coating 1-q Al q The grain size of N is no greater than 2.5 μm. As an example, the Ti in the titanium aluminum nitride coating... 1-q Al q The grain size of N can be any one of the following values or a range between any two: 1.00 μm, 1.17 μm, 1.33 μm, 1.50 μm, 1.67 μm, 1.83 μm, 2.00 μm, 2.17 μm, 2.33 μm, and 2.50 μm.
[0087] In some embodiments, the hardness of the titanium aluminum nitride coating is not less than 30 GPa. As an example, the hardness of the titanium aluminum nitride coating can be any one of 30 GPa, 40 GPa, 50 GPa, 60 GPa, 70 GPa, or a range between any two.
[0088] In some embodiments, the surface roughness Ra of the titanium aluminum nitride coating is not less than 200 nm. As an example, the surface roughness Ra of the titanium aluminum nitride coating can be any one of 200 nm, 250 nm, 300 nm, 350 nm, or a range between any two.
[0089] In some embodiments, the compressive stress of the titanium aluminum nitride coating is 0.5 GPa-3 GPa. As an example, the compressive stress of the titanium aluminum nitride coating can be any one of 0.5 GPa, 1 GPa, 2 GPa, 3 GPa, or a range between any two.
[0090] Therefore, titanium aluminum nitride coatings can significantly improve hardness by utilizing the fine-grain strengthening effect brought about by low grain size. Simultaneously, the high hardness of titanium aluminum nitride coatings greatly enhances the coating's resistance to plastic deformation and wear. The moderate compressive stress of titanium aluminum nitride coatings makes them less prone to peeling and effectively inhibits the formation of coating cracks.
[0091] In some embodiments, the thickness of the titanium aluminum nitride coating is 0.5 μm-30 μm. As an example, the thickness of the titanium aluminum nitride coating can be any one of the following values or a range between any two: 0.5 μm, 1.0 μm, 2.0 μm, 3.0 μm, 4.0 μm, 5.0 μm, 6.0 μm, 7.0 μm, 8.0 μm, 9.0 μm, 10.0 μm, 11.0 μm, 12.0 μm, 13.0 μm, 14.0 μm, 15.0 μm, 16.0 μm, 17.0 μm, 18.0 μm, 19.0 μm, 20.0 μm, 21.0 μm, 22.0 μm, 23.0 μm, 24.0 μm, 25.0 μm, 26.0 μm, 27.0 μm, 28.0 μm, 29.0 μm, and 30.0 μm.
[0092] In some embodiments, the sum of the thicknesses of the alternating monolayers and the adjacent monolayer spacers is 100nm-1000nm. As an example, the sum of the thicknesses of the alternating monolayers and the adjacent monolayer spacers can be any one of 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, and 1000nm, or a range between any two.
[0093] In some embodiments, the thickness of the first sublayer is 1nm-20nm. As an example, the thickness of the first sublayer can be any one of 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, or 20nm, or a range between any two.
[0094] In some embodiments, the thickness of a single second sublayer is 0.5 nm to 10 nm. As an example, the thickness of a single second sublayer can be any one of 0.5 nm, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, and 10 nm, or a range between any two.
[0095] In some embodiments, the thickness of a single spacer layer is 20nm-300nm. As an example, the thickness of a single spacer layer can be any one of 20nm, 40nm, 60nm, 80nm, 100nm, 120nm, 140nm, 160nm, 180nm, 200nm, 220nm, 240nm, 260nm, 280nm, or 300nm, or a range between any two.
[0096] Therefore, by limiting the thickness of each layer, the structural stability of the titanium nitride aluminum coating is improved, and the titanium nitride aluminum coating can have high oxidation resistance, thermal stability and high strength and toughness.
[0097] In some embodiments, the coating further includes: a base coat located between the substrate and the titanium aluminum nitride coating, the base coat including a nitride coating; and / or a functional layer located on the side of the titanium aluminum nitride coating away from the substrate, the functional layer including one or more of a nitride coating and an antioxidant coating, the antioxidant coating including one or more of an alumina coating and a zirconium oxide coating.
[0098] In some embodiments, the nitride coating includes one or more of titanium nitride coating, titanium carbonitride coating, zirconium nitride coating, and zirconium carbonitride coating. Therefore, by setting a base layer in the coating, the corrosion of the substrate by ammonia gas during the vapor deposition of titanium nitride aluminum coating can be reduced, better protecting the integrity of the substrate. The titanium nitride coating and titanium nitride aluminum coating have good lattice matching and compositional compatibility, providing a stable adhesion substrate for the nucleation and growth of the titanium nitride aluminum coating, significantly improving the overall film-substrate adhesion and structural stability of the coating. In the functional layer, the nitride coating acts as a transition layer, alleviating the structural mismatch between the titanium nitride aluminum coating and the anti-oxidation coating. The anti-oxidation coating enhances the coating's resistance to high-temperature oxidation, and the outermost nitride coating improves the coating's wear resistance and also serves a decorative purpose.
[0099] In some embodiments, the underlayer includes a first titanium nitride coating (TiN-1), which is located on one side of the substrate. The thickness of the first titanium nitride coating is 0.1 μm to 1.0 μm. As an example, the thickness of the first titanium nitride coating can be any one of 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, and 1.0 μm, or a range between any two.
[0100] In some embodiments, the underlayer includes a titanium carbonitride (TiCN) coating, which is located on the side of the first titanium nitride coating away from the substrate. The thickness of the titanium carbonitride coating is 0.2 μm to 1.2 μm. As an example, the thickness of the titanium carbonitride coating can be any one of 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, or 1.2 μm, or a range between any two.
[0101] In some embodiments, the undercoat includes a second titanium nitride coating (TiN-2), which is located on the side of the titanium carbonitride coating away from the first titanium nitride coating. The thickness of the second titanium nitride coating is 0.1 μm to 0.5 μm. As an example, the thickness of the second titanium nitride coating can be any one of 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, or 0.5 μm, or a range between any two.
[0102] In some embodiments, the functional layer includes a third titanium nitride coating (TiN-3), which is located on the side of the titanium aluminum nitride coating away from the substrate. The thickness of the third titanium nitride coating is 0.1 μm to 0.5 μm. As an example, the thickness of the third titanium nitride coating can be any one of 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, or 0.5 μm, or a range between any two.
[0103] In some embodiments, the functional layer includes a titanium aluminum oxycarbonate (TiAlOCN) coating, which is located on the side of the third titanium nitride coating away from the substrate. The thickness of the titanium aluminum oxycarbonate coating is 0.1 μm to 0.5 μm. As an example, the thickness of the titanium aluminum oxycarbonate coating can be any one of 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, or 0.5 μm, or a range between any two.
[0104] In some embodiments, the antioxidant coating is located on the side of the aluminum oxide titanium carbonitride coating away from the substrate. The antioxidant coating includes an aluminum oxide coating (Al2O3), and the thickness of the antioxidant coating is 0.1 μm-1 μm. As an example, the thickness of the antioxidant coating can be any one of 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, and 1.0 μm, or a range between any two.
[0105] In some embodiments, the functional layer includes a fourth titanium nitride coating (TiN-4), which is located on the side of the antioxidant coating away from the substrate. The thickness of the fourth titanium nitride coating is 0.1 μm-1 μm. As an example, the thickness of the fourth titanium nitride coating can be any one of 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, and 1.0 μm, or a range between any two.
[0106] In some embodiments, the thickness of the coating is 0.5 μm-30 μm. As an example, the thickness of the coating can be any one of the following values, or a range between any two: 0.5 μm, 1.0 μm, 2.0 μm, 3.0 μm, 4.0 μm, 5.0 μm, 6.0 μm, 7.0 μm, 8.0 μm, 9.0 μm, 10.0 μm, 11.0 μm, 12.0 μm, 13.0 μm, 14.0 μm, 15.0 μm, 16.0 μm, 17.0 μm, 18.0 μm, 19.0 μm, 20.0 μm, 21.0 μm, 22.0 μm, 23.0 μm, 24.0 μm, 25.0 μm, 26.0 μm, 27.0 μm, 28.0 μm, 29.0 μm, and 30.0 μm.
[0107] In a second aspect of this application, a method for preparing the aforementioned cutting tool is provided, comprising: performing a vapor deposition treatment on a substrate to obtain a titanium aluminum nitride coating to obtain the cutting tool.
[0108] In some embodiments, the vapor deposition process includes alternating first vapor deposition process and second vapor deposition process, wherein the gas in the first vapor deposition process includes TiCl4, AlCl3, NH3, and H2, and the gas in the second vapor deposition process includes TiCl4, NH3, H2, and optionally AlCl3.
[0109] In some embodiments, the gas volume of the first vapor deposition process is used as a basis, including 0.03%-0.08% TiCl4, 0.20%-0.70% AlCl3, and 0.80%-1.20% NH3.
[0110] As an example, based on the total gas volume of the first vapor deposition process, the volume fraction of TiCl4 can be any one of 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, or 0.08%, or a range between any two.
[0111] As an example, based on the total gas volume of the first vapor deposition process, the volume fraction of AlCl3 can be any one of 0.20%, 0.30%, 0.40%, 0.50%, 0.60%, or 0.70%, or a range between any two.
[0112] As an example, based on the total gas volume of the first vapor deposition process, the volume fraction of NH3 can be any one of 0.80%, 0.90%, 1.0%, 1.1%, 1.2%, or a range between any two.
[0113] In some embodiments, the gas volume of the second vapor deposition process is used as a basis, including 0.03%-0.08% TiCl4, 0%-0.30% AlCl3, and 0.80%-1.20% NH3.
[0114] As an example, based on the total gas volume of the second vapor deposition process, the volume fraction of TiCl4 can be any one of 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, or 0.08%, or a range between any two.
[0115] As an example, based on the total gas volume of the second vapor deposition process, the volume fraction of AlCl3 can be any one of 0%, 0.1%, 0.2%, 0.3%, or a range between any two.
[0116] As an example, based on the total gas volume of the second vapor deposition process, the volume fraction of NH3 can be any one of 0.80%, 0.90%, 1.0%, 1.1%, 1.2%, or a range between any two.
[0117] Therefore, by adjusting the AlCl3 gas flow rate of the first and second vapor deposition processes, alternating and spaced layers of titanium nitride aluminum coatings with different aluminum contents can be obtained. A high-aluminum-content titanium nitride aluminum coating was obtained by chemical vapor deposition, which effectively improved the hardness and oxidation resistance of the titanium nitride aluminum coating and extended the service life of cutting tools.
[0118] In some embodiments, the diameter of the first vent hole in the central graphite gas pipe of the chemical vapor deposition furnace is 1 mm to 2 mm. As an example, the diameter of the first vent hole in the central graphite gas pipe of the chemical vapor deposition furnace can be any one of 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, 2.0 mm, or a range between any two.
[0119] In some embodiments, the aperture of the second vent hole in the central graphite gas pipe of the chemical vapor deposition furnace is 2mm-3mm. As an example, the aperture of the second vent hole in the central graphite gas pipe of the chemical vapor deposition furnace can be any one of 2.0mm, 2.1mm, 2.2mm, 2.3mm, 2.4mm, 2.5mm, 2.6mm, 2.7mm, 2.8mm, 2.9mm, or 3.0mm, or a range between any two.
[0120] In some embodiments, the rotational speed of the central graphite gas tube of the chemical vapor deposition furnace is 1 r / min to 10 r / min. As an example, the rotational speed of the central graphite gas tube of the chemical vapor deposition furnace can be any one of 1 r / min, 2 r / min, 3 r / min, 4 r / min, 5 r / min, 6 r / min, 7 r / min, 8 r / min, 9 r / min, and 10 r / min, or a range between any two.
[0121] Therefore, by controlling the rotational speed of the graphite central gas tube, the thickness of the alternating layers of the titanium nitride aluminum coating can be controlled.
[0122] In some embodiments, the deposition temperature of the first vapor deposition process is 700°C-800°C. As an example, the deposition temperature of the first vapor deposition process can be any one of 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, and 800°C, or a range between any two.
[0123] In some embodiments, the deposition pressure of the first vapor deposition process is 2 mbar to 15 mbar. As an example, the deposition pressure of the first vapor deposition process can be any one of 2 mbar, 3 mbar, 4 mbar, 5 mbar, 6 mbar, 7 mbar, 8 mbar, 9 mbar, 10 mbar, 11 mbar, 12 mbar, 13 mbar, 14 mbar, or 15 mbar, or a range between any two.
[0124] In some embodiments, the deposition time of the first vapor deposition treatment is 1 min to 30 min. As an example, the deposition time of the first vapor deposition treatment can be any one of 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min, and 30 min, or a range between any two.
[0125] In some embodiments, the deposition temperature of the second vapor deposition process is 730°C-800°C. As an example, the deposition temperature of the second vapor deposition process can be any one of 730°C, 735°C, 740°C, 745°C, 750°C, 755°C, 760°C, 765°C, 770°C, 775°C, 780°C, 785°C, 790°C, 795°C, or 800°C, or a range between any two.
[0126] In some embodiments, the deposition pressure of the second vapor deposition process is 2 mbar to 15 mbar. As an example, the deposition pressure of the second vapor deposition process can be any one of 2 mbar, 3 mbar, 4 mbar, 5 mbar, 6 mbar, 7 mbar, 8 mbar, 9 mbar, 10 mbar, 11 mbar, 12 mbar, 13 mbar, 14 mbar, or 15 mbar, or a range between any two.
[0127] In some embodiments, the deposition time of the second vapor deposition process is 0.2 min to 3 min. As an example, the deposition time of the second vapor deposition process can be any one of 0.2 min, 1 min, 2 min, and 3 min, or a range between any two.
[0128] In some embodiments, the first vapor deposition process and the second vapor deposition process are alternated 5 to 100 times. As an example, the number of times the first vapor deposition process and the second vapor deposition process are alternated can be any one of 5, 15, 25, 35, 45, 55, 65, 75, 85, 95, and 100 times.
[0129] Therefore, by adjusting the deposition parameters of the first vapor deposition process and the second vapor deposition process, a titanium aluminum nitride coating with a periodic layered stacking structure can be obtained.
[0130] In some embodiments, prior to performing vapor deposition on the substrate, the method further includes: performing vapor deposition on the substrate to form an underlayer, the underlayer being located on at least a portion of the surface of the substrate and between the substrate and the titanium aluminum nitride coating; and / or, after performing vapor deposition on the substrate, the method further includes: performing a third vapor deposition on the side of the titanium aluminum nitride coating away from the substrate to form a functional layer, the functional layer including one or more of a nitride coating and an antioxidant coating, the antioxidant coating including one or more of an alumina coating and a zirconium oxide coating.
[0131] Therefore, by performing vapor deposition to obtain the underlayer before preparing the titanium aluminum nitride coating, the protective effect on the substrate can be better exerted. After preparing the titanium aluminum nitride coating, vapor deposition is performed to obtain the functional layer, which is beneficial to improving the coating's anti-oxidation performance, wear resistance, and decorative performance. The titanium aluminum nitride coating, the underlayer, and the functional layer together improve the overall adhesion and stability of the coating.
[0132] The description of the various embodiments above tends to emphasize the differences between the various embodiments. The similarities or similarities between them can be referred to, and for the sake of brevity, they will not be repeated here.
[0133] The following specific embodiments illustrate the solution of this application. It should be noted that these embodiments are for illustrative purposes only and should not be considered as limiting the scope of this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0134] Example 1 Eight layers of cemented carbide indexable insert XNMU 070508-MM4 were coated by vapor deposition. The cemented carbide composition was 10% Co and the balance was tungsten carbide (WC). The thickness of these eight layers was approximately 7.6 μm. The coating order from closest to furthest from the substrate was: underlayer (TiN-1 (approx. 0.2 μm), TiCN (approx. 0.8 μm), TiN-2 (approx. 0.2 μm)), titanium aluminum nitride coating (Ti... 0.17 Al 0.83 N (approximately 5 μm)), functional layers (TiN-3 (approximately 0.1 μm), TiAlOCN (approximately 0.2 μm), Al2O3 (approximately 1.0 μm), TiN-4 (approximately 0.1 μm)). Sample A was obtained, and the process parameters for each layer are shown in the table below: Table 1 Process parameters of sample A
[0135] Example 2 Eight layers of cemented carbide indexable insert XNMU 070508-MM4 were coated by vapor deposition. The cemented carbide composition was 10% Co and the balance was tungsten carbide (WC). The thickness of these eight layers was approximately 7.6 μm. The coating order from closest to furthest from the substrate was: underlayer (TiN-1 (approx. 0.2 μm), TiCN (approx. 0.8 μm), TiN-2 (approx. 0.2 μm)), titanium aluminum nitride coating (Ti... 0.17 Al 0.83 N (approximately 5 μm)), functional layers (TiN-3 (approximately 0.1 μm), TiAlOCN (approximately 0.2 μm), Al2O3 (approximately 1.0 μm), TiN-4 (approximately 0.1 μm)). Sample B was obtained, and the process parameters for each layer are shown in the table below: Table 2 Process parameters of sample B
[0136] Example 3 Eight layers of cemented carbide indexable insert XNMU 070508-MM4 were coated by vapor deposition. The cemented carbide composition was 10% Co and the balance was tungsten carbide (WC). The thickness of these eight layers was approximately 7.6 μm. The coating order from closest to furthest from the substrate was: underlayer (TiN-1 (approx. 0.2 μm), TiCN (approx. 0.8 μm), TiN-2 (approx. 0.2 μm)), titanium aluminum nitride coating (Ti... 0.17 Al 0.83 N (approximately 5 μm)), functional layers (TiN-3 (approximately 0.1 μm), TiAlOCN (approximately 0.2 μm), Al2O3 (approximately 1.0 μm), TiN-4 (approximately 0.1 μm)). Sample C was obtained, and the process parameters for each layer are shown in the table below: Table 3 Process parameters of sample C
[0137] Example 4 Eight layers of cemented carbide indexable insert XNMU 070508-MM4 were coated by vapor deposition. The cemented carbide composition was 10% Co and the balance was tungsten carbide (WC). The thickness of these eight layers was approximately 7.6 μm. The coating order from closest to furthest from the substrate was: underlayer (TiN-1 (approx. 0.2 μm), TiCN (approx. 0.8 μm), TiN-2 (approx. 0.2 μm)), titanium aluminum nitride coating (Ti... 0.17 Al 0.83N (approximately 5 μm)), functional layers (TiN-3 (approximately 0.1 μm), TiAlOCN (approximately 0.2 μm), Al2O3 (approximately 1.0 μm), TiN-4 (approximately 0.1 μm)). Sample D was obtained, and the process parameters for each layer are shown in the table below: Table 4 Process parameters of sample D
[0138] Comparative Example 1 Eight layers of cemented carbide indexable insert XNMU 070508-MM4 were coated by vapor deposition. The cemented carbide composition was 10% Co and the balance was tungsten carbide (WC). The thickness of these eight layers was approximately 7.6 μm. The coating order from closest to furthest from the substrate was: underlayer (TiN-1 (approx. 0.2 μm), TiCN (approx. 0.8 μm), TiN-2 (approx. 0.2 μm)), titanium aluminum nitride coating (Ti... 0.20 Al 0.80 N (approximately 5 μm)), functional layers (TiN-3 (approximately 0.1 μm), TiAlOCN (approximately 0.2 μm), Al2O3 (approximately 1.0 μm), TiN-4 (approximately 0.1 μm)). Sample E was obtained, and the process parameters for each layer are shown in the table below: Table 5 Process parameters of sample E
[0139] Test methods and results: The operation is milling, the workpiece is a cuboid block, the insert type is XNMU 070508-MM4, the cutting speed is 150m / min, the feed is 0.15mm / rev, and the depth of cut is 2.0mm.
[0140] The failure criterion will be that the wear amount VB on the cutting edge is greater than 0.3mm.
[0141] 1. Test of cutting cast iron with cutting tool (dry cutting): The cutting material is cast iron.
[0142] Table 6. Dry milling life of different cast iron samples
[0143] 2. Cutting test of cast iron with cutting tool (wet cutting): The cutting material is cast iron.
[0144] Table 7 Wet milling life of different cast iron samples
[0145] 3. Test of cutting alloy steel with cutting tools (dry cutting) The cutting material is alloy steel.
[0146] Table 8. Dry milling life of alloy steel samples for different samples
[0147] 4. Wet cutting test of alloy steel using cutting tools The cutting material is alloy steel.
[0148] Table 9 Wet milling life of different alloy steel samples
[0149] 5. Test of cutting stainless steel with a cutting tool (dry cutting) The cutting material is stainless steel.
[0150] Table 10 Dry milling life of stainless steel samples
[0151] 6. Wet cutting test of stainless steel using cutting tools The cutting material is stainless steel.
[0152] Table 11 Wet milling life of stainless steel samples for different samples
[0153] Therefore, under the same cutting conditions, samples A, B, C, and D have higher aluminum content than sample E, but their cutting life is significantly higher. This indicates that the titanium-aluminum nitride coating with a periodic layered structure obtained by alternating first and second vapor deposition processes achieves high aluminum content while significantly improving the chipping resistance, wear resistance, and cutting life of the cutting tool. The cutting life of sample A is higher than that of sample B, and that of sample C is higher than that of sample D. This suggests that the more times the first and second vapor deposition processes are alternated, the better the effect on improving the cutting tool's life. The cutting life of sample A is higher than that of sample C, and that of sample B is higher than that of sample D. This suggests that, given the same number of alternations between the first and second vapor deposition processes, a lower AlCl3 content during the second vapor deposition process is more conducive to improving the cutting life of the sample.
[0154] refer to Figure 1 It can be seen that the coating of sample A contains Ti. 0.17 Al 0.83 N coating and Al2O3 coating.
[0155] refer to Figure 2 It can be seen that the Al2O3 layer in the coating of sample A is similar to cauliflower.
[0156] refer to Figure 3 It can be seen that the Ti of sample A0.17 Al 0.83 The surface of the N-coated grains has a triangular pyramidal shape.
[0157] refer to Figure 4 It can be seen that the Ti of sample A 0.17 Al 0.83 The N coating exhibits a continuous zigzag shape in its cross-section.
[0158] refer to Figure 5 It can be seen that the Ti of sample A 0.17 Al 0.83 In the N coating, the periodic layered stacking structure presents an inverted V-shape in the cross-section of the coating grains.
[0159] refer to Figure 6 It can be seen that the Ti of sample A 0.17 Al 0.83 The thicknesses of the first and second sublayers in the N coating are 10 nm and 2 nm, respectively.
[0160] refer to Figure 7 It can be seen that the Ti of sample A 0.17 Al 0.83 The N coating has a face-centered cubic structure with grains growing along the
[111] direction.
[0161] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A cutting tool, characterized in that, include: Substrate; A coating, the coating being located on at least a portion of the surface of the substrate, the coating comprising: Titanium aluminum nitride coating, wherein the titanium aluminum nitride coating comprises: Ti 1-q Al q N, 0.7 ≤ q < 1, the titanium aluminum nitride coating comprises alternating layers and spacer layers stacked alternately, the absolute value of the difference between the number of alternating layers and the number of spacer layers is not greater than 1, the alternating layer comprises alternating first sub-layers and second sub-layers stacked alternately, the absolute value of the difference between the number of first sub-layers and the number of second sub-layers is not greater than 1, the first sub-layer comprises Ti 1-x Al x N, 0.6 ≤ x ≤ 0.95, the second sublayer includes Ti 1-y Al y N, 0.1≤y≤0.5, the spacer layer includes Ti 1-z Al z For N, 0≤z≤0.1, the lattice mismatch between the first sublayer and the second sublayer is 0.4%-4.2%; the lattice mismatch between the first sublayer and the spacer layer is 2.0%-4.6%; and the lattice mismatch between the second sublayer and the spacer layer is 0%-2.4%.
2. The cutting tool according to claim 1, characterized in that, The number of alternating layers is 5 to 100; and / or, The first sub-layer has 8 to 200 layers; and / or, Ti in the first sub-layer 1-x Al x N, Ti in the second sublayer 1-y Al y N, Ti in the spacer layer 1-z Al z N is a face-centered cubic structure, each independently.
3. The cutting tool according to claim 1 or 2, characterized in that, The crystal plane relationship between the first sublayer and the second sublayer is {001}Ti 1-x Al x N / / {001}Ti 1-y Al y N; and / or, the crystal plane relationship between the first sublayer and the spacer layer is {001}Ti. 1-x Al x N / / {001}Ti 1-z Al z N; and / or, the crystal plane relationship between the second sublayer and the spacer layer is {001}Ti. 1-y Al y N / / {001}Ti 1-z Al z N; and / or, the crystal orientation relationship between the first sublayer and the second sublayer is as follows: <010> Ti 1-x Al x N / / <010> Ti 1-y Al y N; and / or, the crystal orientation relationship between the first sublayer and the spacer layer is: <010> Ti 1- x Al x N / / <010> Ti 1-z Al z N; and / or, the crystal orientation relationship between the second sublayer and the spacer layer is as follows: <010> Ti 1-y Al y N / / <010> Ti 1-z Al z N.
4. The cutting tool according to claim 1 or 2, characterized in that, Taking the surface of the titanium aluminum nitride coating away from the substrate as a first plane, a second plane parallel to the first plane is located on the side of the first plane facing the substrate. The minimum distance between the first plane and the second plane is no greater than 60% of the thickness of the titanium aluminum nitride coating. The titanium aluminum nitride coating, along any polished section on the second plane... <111> The cross-sectional area of grains with a crystal orientation and an angle less than 10° with the normal of the first plane accounts for not less than 60% of the total cross-sectional area of the grains; and / or, the texture coefficients TC(200) on the (200) crystal plane, TC(220) on the (220) crystal plane, TC(311) on the (311) crystal plane, TC(331) on the (331) crystal plane, TC(420) on the (420) crystal plane, and TC(111) on the (111) crystal plane satisfy the following: TC(200)≤0.5, 0.2≤TC(220)≤0.7, 0.5≤TC(311)≤1, TC(331)≤0.5, TC(420)≤0.5, TC(111) / TC(311)≥3.
5. The cutting tool according to claim 1 or 2, characterized in that, The Ti in the titanium aluminum nitride coating 1-q Al q The grain size of N is not greater than 2.5 μm; and / or the hardness of the titanium aluminum nitride coating is not less than 30 GPa; and / or the compressive stress of the titanium aluminum nitride coating is 0.5 GPa-3 GPa.
6. The cutting tool according to claim 1 or 2, characterized in that, The thickness of the titanium aluminum nitride coating is 0.5 μm-30 μm; and / or, the sum of the thicknesses of the alternating single layer and the adjacent single spacer layer is 100 nm-1000 nm; and / or, the thickness of the first sublayer is 1 nm-20 nm; and / or, the thickness of the second sublayer is 0.5 nm-10 nm; and / or, the thickness of the spacer layer is 20 nm-300 nm.
7. The cutting tool according to claim 1 or 2, characterized in that, The coating also includes: A primer layer, wherein the primer layer is located between the substrate and the titanium aluminum nitride coating, and the primer layer includes a nitride coating; and / or, A functional layer is located on the side of the titanium aluminum nitride coating away from the substrate. The functional layer includes one or more of a nitride coating and an antioxidant coating. The antioxidant coating includes one or more of an aluminum oxide coating and a zirconium oxide coating.
8. A method for preparing the cutting tool according to any one of claims 1-7, characterized in that, include: A vapor phase deposition process is performed on the substrate to obtain a titanium aluminum nitride coating, which is then used to obtain a cutting tool. The vapor deposition process includes alternating first vapor deposition and second vapor deposition processes. The first vapor deposition process uses gases comprising TiCl4, AlCl3, NH3, and H2. The second vapor deposition process uses gases comprising TiCl4, NH3, H2, and optionally AlCl3. Based on the total volume of gases in the first vapor deposition process, the mixture includes 0.03%-0.08% TiCl4, 0.20%-0.70% AlCl3, and 0.80%-1.20% NH3. Based on the total volume of gases in the second vapor deposition process, the mixture includes 0.03%-0.08% TiCl4, 0%-0.30% AlCl3, and 0.80%-1.20% NH3.
9. The method according to claim 8, characterized in that, The deposition temperature of the first vapor deposition treatment is 700℃-800℃, the deposition pressure of the first vapor deposition treatment is 2mbar-15mbar, and the deposition time of the first vapor deposition treatment is 1min-30min; and / or, the deposition temperature of the second vapor deposition treatment is 730℃-800℃, the deposition pressure of the second vapor deposition treatment is 2mbar-15mbar, and the deposition time of the second vapor deposition treatment is 0.2min-3min; and / or, the number of times the first vapor deposition treatment and the second vapor deposition treatment are alternated is 5-100 times.
10. The method according to claim 8 or 9, characterized in that, The method further includes, prior to performing vapor deposition on the substrate, performing vapor deposition on the substrate to form an underlayer, the underlayer being located at least a portion of the surface of the substrate and between the substrate and the titanium aluminum nitride coating; and / or, The process of performing vapor deposition on the substrate further includes performing a third vapor deposition on the side of the titanium aluminum nitride coating away from the substrate to form a functional layer. The functional layer includes one or more of a nitride coating and an anti-oxidation coating. The anti-oxidation coating includes one or more of an alumina coating and a zirconium oxide coating.
